2012
DOI: 10.1007/128_2012_398
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Dendritic Dipeptides as a Model of Chiral Selection in Primitive Biological Systems

Abstract: Biological macromolecules are homochiral, composed of sequences of stereocenters possessing the same repeated absolute configuration. This chapter addresses the mechanism of homochiral selection in polypeptides. In particular, the relationship between the stereochemistry (L or D) of structurally distinct α-amino acids is explored. Through functionalization of Tyr-Xaa dipeptides with self-assembling dendrons, the effect of stereochemical sequence of the dipeptide on the thermodynamics of self-assembly and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 94 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Recently, Conejero-Muriel et al have demonstrated the effect of the supramolecular chirality of short peptide hydrogels on protein crystallogenesis 31 . Moreover, the effects of solvents and the participation of chiral guests on the supramolecular chirality of peptide-based organogelators were reported previously 32 33 34 35 . Here, we report, for the first time, the inversion of chirality by fluorinated peptide-based gelators that contain two fluorine atoms, upon sonication-induced organogelation.…”
mentioning
confidence: 90%
“…Recently, Conejero-Muriel et al have demonstrated the effect of the supramolecular chirality of short peptide hydrogels on protein crystallogenesis 31 . Moreover, the effects of solvents and the participation of chiral guests on the supramolecular chirality of peptide-based organogelators were reported previously 32 33 34 35 . Here, we report, for the first time, the inversion of chirality by fluorinated peptide-based gelators that contain two fluorine atoms, upon sonication-induced organogelation.…”
mentioning
confidence: 90%
“…12 Supramolecular deracemization does not occur in systems with strong intermolecular interactions, such as chiral dendritic dipeptides, 13 which instead give lower order assemblies when not enantiopure. 14 Indeed, incomplete deracemization of mixtures of hat-shaped molecules containing inseparable, diastereomeric combinations of stereocenters gave reduced order in the crystal state. This observation is analogous to the amorphous nature of atactic poly(propylene) compared to the crystallinity of its isotactic counterpart.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The mechanism of deracemization, which depended on weak interactions between individual molecules, could only be understood using solid-state NMR . Supramolecular deracemization does not occur in systems with strong intermolecular interactions, such as chiral dendritic dipeptides, which instead give lower order assemblies when not enantiopure . Indeed, incomplete deracemization of mixtures of hat-shaped molecules containing inseparable, diastereomeric combinations of stereocenters gave reduced order in the crystal state.…”
Section: Introductionmentioning
confidence: 99%
“…Greater control over molecular structure can be gained by combining peptides with dendrons 20, 21 or other sequence-defined polymers. The diverse pool of α-amino acid monomers can enrich the programmable functionality of dendrons by conferring chirality, 2224 molecular recognition, 25 surface adsorption, 26 and stimulus responsive properties 2733 to peptide-dendron hybrids. The homogeneity of hybrids obtained from monodisperse polymers may be advantageous for applications as therapeutics.…”
Section: Introductionmentioning
confidence: 99%